OBSTACLES IN IMPLEMENTING INNOVATIVE LEARNING METHODS AT SDN 8 SUBULUSSALAM - Hermalinda; Siti Mayang Sari; Fitriani Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Education is the main foundation for a country's development, and to improvethe quality of education, the use of innovative learning methods is a must.However, obstacles arise in its implementation, including limited supportinginfrastructure, limited skills and knowledge of teaching staff, and limitedavailability of learning resources. The main obstacles involve limitedinfrastructure, training needs for teaching staff, availability of learningresources that support innovation, resistance from stakeholders, and uniquelocal cultural contexts. This research aims to describe the obstacles inimplementing innovative learning methods at SDN 8 Subulussalam. Thisresearch uses a qualitative approach, descriptive research type. Based on theresearch results, it can be concluded that SDN 8 Subulussalam faces significantchallenges in implementing innovative learning methods. These obstaclesinclude limited infrastructure, limited skills and knowledge of teaching staff, aswell as limited availability of learning resources. Efforts to overcome theselimitations involve improving facilities with support from related parties andeffective budget management strategies. Empowering teachers is a priority, byproviding regular training and coaching.